2022
DOI: 10.1111/aphw.12344
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal effects of COVID‐19‐related stressors on young adults' mental health and wellbeing

Abstract: The COVID‐19 pandemic has presented young adults with novel challenges and disruptions to several life domains. The current study examined how COVID‐19‐related stressors (i.e., job‐related, financial‐related, social/relational, and illness‐related stressors) relate to young adults' symptoms of depression and anxiety, and satisfaction with life (in the US). In Aim 1, we examined associations between COVID‐19‐related stressors and indices of mental health and well‐being in the initial phase of the pandemic (Apri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 32 publications
5
37
0
Order By: Relevance
“…Indeed, in the last two years, scientific research has highlighted that in the emerging adulthood individuals present heightened levels of psychological difficulties, including symptoms of distress, anxiety, and depression (Panzeri et al, 2021 ; Parola et al, 2020 ). Importantly, emerging adulthood may expose to a higher risk of developing psychological issues because individuals in this part of the lifespan go through a process of individualization, structuring self-esteem, and personal growth (van den Berg et al, 2021 ) – in which they progressively rediscuss and strengthen their role in the society, relationships, and the professional field (Graupensperger et al, 2022 ). Thus, the trauma associated with the pandemic situation and its limitations may have disrupted this process, hence hindering the possibility to fulfill personal, professional, and relational wills (Cao et al, 2020 ; Cheng et al, 2014 ; Zhang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, in the last two years, scientific research has highlighted that in the emerging adulthood individuals present heightened levels of psychological difficulties, including symptoms of distress, anxiety, and depression (Panzeri et al, 2021 ; Parola et al, 2020 ). Importantly, emerging adulthood may expose to a higher risk of developing psychological issues because individuals in this part of the lifespan go through a process of individualization, structuring self-esteem, and personal growth (van den Berg et al, 2021 ) – in which they progressively rediscuss and strengthen their role in the society, relationships, and the professional field (Graupensperger et al, 2022 ). Thus, the trauma associated with the pandemic situation and its limitations may have disrupted this process, hence hindering the possibility to fulfill personal, professional, and relational wills (Cao et al, 2020 ; Cheng et al, 2014 ; Zhang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Somewhat consistent with previous research [ 15 , 35 ], we found significant increases in some reports of depressive symptoms, reductions in substance use, reductions in physical and sexual activity, and reductions in food insecurity ( Table 1 ). In concert with prior work examining changes in perceived norms and motivations for use [ 36 ]–particularly increases in using substances to cope [ 37 ]–it is clear that psychosocial risk factors for and prevalence of health behaviors have evolved across the pandemic. A critical contribution of the current study was the use of LCA to consider a broad set of indicators of health and well-being simultaneously, at each timepoint, and examine change over time.…”
Section: Discussionmentioning
confidence: 93%
“…Taking the broader student experiences into consideration can inform more efficient, tailored supports for college students that meet them where they are, with the services that they need. These findings are particularly salient in light of emerging longitudinal evidence findings that the effects of COVID-19 have direct and enduring impacts on mental health and well-being (e.g., [ 36 ]).…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, COVID-related stress increased over time, with its peak being observed in the third wave of data collection (late 2021). Stressors, their intensity as well as their qualitative aspects have changed during the pandemic (see ( 76 , 77 ), and a fluctuation of stress related to the pandemic is thus natural ( 78 ). Consequently, there is a possibility of an interplay between COVID-related stress and COVID-related anxiety.…”
Section: Discussionmentioning
confidence: 99%